The VA National TeleNeurology Program implementation: a mixed-methods evaluation guided by RE-AIM framework - Damush, Teresa M.; Wilkinson, Jayne R.; Martin, Holly; Miech, Edward J.; Tang, Qing; Taylor, Stanley; Daggy, Joanne K.; Bastin, Grace; Islam, Robin; Myers, Laura J.; Penney, Lauren S.; Narechania, Aditi; et al. (Frontiers in Health Services, 2023)
Introduction: The VA Office of Rural Health (ORH) funded the Veterans Health Administration (VHA) National TeleNeurology Program (NTNP) as an Enterprise-Wide Initiative (EWI). NTNP is an innovative healthcare delivery model designed to fill the patient access gap for outpatient neurological care especially for Veterans residing in rural communities. The specific aim was to apply the RE-AIM framework in a pragmatic evaluation of NTNP services. Materials and Methods: We conducted a prospective implementation evaluation. Guided by the pragmatic application of the RE-AIM framework, we conceptualized a mixed-methods evaluation for key metrics: 1. Reach into the Veteran patient population assessed as total NTNP new patient consult volume and total NTNP clinical encounters (new and return); 2. Adoption and implementation by VA sites through site staff and NTNP interviews; 3. Effectiveness through configurational analysis of conditions leading to high Veteran satisfaction and referring providers perceived effectiveness; 4. Implementation success through perceived management, implementation barriers, facilitators and adaptations, through rapid qualitative analysis of multiple stakeholders' assessments; and 5. NTNP maintenance through monitoring quarterly TeleNeurology consultation volume.Results: NTNP was successfully implemented in 13 VAMCs over two years. The total NTNP new patient consult volume was in FY21 was 836 (58% rurally residing); this increased to 1706 in FY22 (55% rurally residing). Total (new and follow up) NTNP clinical encounters were 1306 in FY21 and 3730 in FY22. Overall, sites reported positive experiences with program implementation and perceived the program was serving Veterans with little access to neurological care. Veterans also reported high satisfaction with the NTNP program. We identified patient level of perceived excellent teleneurologist-patient communications; reduced need to drive to get care; and that NTNP provided care that the Veteran otherwise could not access as key factors related to high Veteran satisfaction.Conclusions: The VA NTNP demonstrated substantial reach, adoption, effectiveness, implementation success and maintenance over the first two years of the program. The NTNP was highly acceptable to both the clinical providers making the referrals and the Veterans receiving the referred video care. The pragmatic application of the RE-AIM framework to guide implementation evaluations is appropriate, comprehensive and recommended for future applications.